Electrodiagnosis in diseases of nerve and muscle : principles and practice - Kimura, Jun (Oxford University Press, 2001)
This volume addresses the specific needs of neurologists interested in non-invasive electrodiagnostic methods, particularly those practicing electromyography (EMG). The book provides a comprehensive review of most peripheral nerve and muscle diseases, including specific techniques and locations for performing each test.